The Relationship Between Selected HRM Practices And Employee Retention With Employee Engagement As A Mediating Factor Among Employees In Construction Sector - Pau, Zhang Jun (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study aims to identify the relationship between selected HRM practices (reward and recognition, career development and benefits) and employee retention with employee engagement as a mediating factor among employees in construction sector. A quantitative study was conducted by using cross-sectional survey method. The pilot study had been carried out that involved 30 respondents and the result depicted high reliability for all questionnaire items with Cronbach’s Alpha value in the range of 0.825 to 0.921. 130 sets of questionnaires were distributed to office employees in the six construction companies and 110 sets were collected back but only 97 sets were useable. Data collected was analyzed using Spearman Correlation and Linear regression analysis. From the data analysis, it was found that there is a moderate positive correlation between reward and recognition, career development and benefits toward employee retention. Furthermore, findings of this study showed that employee engagement has mediated the relationship between three selected HRM practices and employee retention. Other than that, implications of this study towards organization, human resource practitioner and theoretical contribution were also discussed. Several recommendations were provided to organization and human resource practitioner as well as future researcher.